Implementation of a pipe failure prediction model as a support tool for water networks management strategies - R. Ramírez; R. Cobacho; D. Torres; P.A. López-Jiménez (Ingeniería del Agua)
The work presented in this paper has a dual objective: on the one hand, reaching reliable estimates for the pipes lifespan in a water distribution network; on the other, doing so by means of a relatively low complex model with relatively low need for historical data. The model is based on using the Weibull distribution over two years of failure records. The results achieved are compared with those provided by the well-known Weibull proportional risk model, that have been applied on the same data sets. The comparison is positive in both the location on the Davis curve obtained for each group of pipes, and the relative error existing between both estimates of future failures.